The Concept of Curriculum, the Nature of Curriculum, and the Islamic Religious Education Curriculum REC - Mara Hamdan Aritonang; Haidar Putra Daulay Haidar; Muhammad Roihan Daulay Roihan (Yayasan Azhar Amanaa Yogyakarta, 2026)
Social change, advances in science, and the dynamics of educational policy demand a clear conceptual understanding of curriculum as a fundamental basis in the implementation of education. In Islamic Religious Education (PAI), the curriculum is not only understood as a learning plan but also as a strategic instrument for developing students’ character, values, and competencies based on Islamic teachings. Therefore, the study of the concept of curriculum, the nature of curriculum, and the Islamic Religious Education curriculum is essential to strengthen both the theoretical foundation and educational practice. This research aims to explain the basic concept of curriculum, the nature of curriculum from an educational perspective, and the characteristics of the Islamic Religious Education curriculum. The method used is library research with a descriptive qualitative approach through the analysis of various literature such as books, scholarly articles, and educational policy documents. The results show that the curriculum is dynamic in nature, not merely a formal document, but also a structured learning experience designed to achieve educational goals. The nature of the curriculum encompasses philosophical, sociological, psychological, and pedagogical aspects that are interrelated. The Islamic Religious Education curriculum has distinct characteristics in integrating the values of creed (aqidah), worship (ibadah), and moral conduct (akhlaq) to form an insan kamil who is faithful, knowledgeable, and of noble character. The contribution of this study provides conceptual strengthening for curriculum developers, educators, and policymakers in designing a more contextual, integrative, and adaptive PAI curriculum in response to contemporary developments, without neglecting Islamic values.